Pre-emptive infrared countermeasures - Jackman, J. (Cranfield University, 2012)
The aim of this PhD is to investigate pre-emptive flare release compared to reactive flare release and their efficacy as a countermeasure device in the protection of fast jet and transport aircraft against the MANPAD threat. Implicit in this is to study the optimum release time of the flare decoy. Consequently, this also raises the question of whether flares of reduced payload size can be as effective as standard flares when released at this optimum time. To achieve these aims the initial step is to develop models for the different types of Man-Portable Air-Defence (MANPAD) systems and the IR seekers they utilise. This also requires the simulation of the full pre-launch process, namely the acquisition of the target to obtain lock-on then the application of lead and super elevation to give a more realistic model of the firing sequence. Two target models are also developed, a fast jet (AMX-A1) and a transport aircraft (C130), with realistic positions and ejection characteristics for the countermeasure (CM) dispensers. The next stage includes a counter-countermeasure (CCM) capability in the IR seekers. The first is a track angle bias with values optimised for the two aircraft models. Second is the development of a two-colour seeker with signal processors designed for both a spinscan and a conscan system. Using all MANPAD models flares are released at intervals throughout the engagements to find the optimum firing time and the simulations repeated for flares with reduced peak intensity and burn time. The results show that flare release around the time of missile launch is effective against most threats, even the more advanced MANPADs with CCMs. Also, that for reduced performance flares maintaining the burn time is perhaps more important than the peak intensity.